ENDOSCOPIC ULTRASOUND GUIDED BIOPSY OF A MEDIASTINAL MASS - Yusuf, Aasim; Khalid, Shahid Raza; Ahmed, Qasim; Faruqui, Zia S (Journal of Ayub Medical College Abbottabad, 2004)
Endoscopic ultrasound (EUS) now has an established role in the diagnosis, staging and management of cancers of the oesophagus, stomach, pancreato-biliary system and rectum. Recently, a role for EUS in the staging of lung cancers has been proposed. Linear EUS allows fine needle aspiration (FNA), core biopsies and therapeutic manoeuvres such as coeliac plexus block to be performed. We present here the first reported EUS-guided biopsy from Pakistan. A patient with probable bronchogenic carcinoma was referred for assessment of operability. A thoracic CT scan showed subcarinal and aorto-pulmonary recess lymphadenopathy. An EUS-guided FNA was performed, confirming metastatic non-small cell lung cancer and rendering the patient inoperable.